Situation Report: Hungary, 19 October 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Fourth National Congress of Industrial Co-Operatives First Agreements under Comecon "Complex Program" Trends in Hungarian Tourism Hungarian-Romanian Relations Minister Clashes with Magyar Nemzet over a Cartoon Allocation Problem Faces Agricultural Co-operatives with Surplus Income Private Plots Still Need Support of Party Organizations Continued Shortage of Machinery on the Private Plots Negotiations with Vatican Gather Momentum